(untitled) (Mustansiria Dental Journal, 2018)
The purpose of this in-vitro study is to evaluate and compare the fracture resistance of endodontically treated teeth restored using cast posts cemented with different types of cement. Thirty intact human maxillary central incisors were selected for this study. The crowns were removed and endodontic therapy were done on the roots, which were then prepared to receive cast posts, after their fabrication, the cast posts were cemented with zinc phosphate cement (group I), resin modified glass ionomer cement (group II),and resin cement (group III). The samples were subjected to compressive fracturing loads by a Zwick testing machine at a cross head speed of 5mm/min., with an angle of 45º to the long axis of the tooth. The results showed that the posts cemented with resin cement exhibited the highest mean failure load followed by posts cemented with resin modified glass ionomer cement , while posts cemented with zinc phosphate cement exhibited the lowest mean failure load.